(untitled) (Conference Zone, 2022)
Global climate change is one of the urgent problems of today, and it is not only the average annual temperature increase on our planet, but also the change of the entire geosystem, the rise of the world ocean level, the melting of glaciers in the mountains, the increase of drought due to the lack of precipitation, the change of the river flow regime and the instability of the climate. other changes are also considered. As a result of global climate change, the area of glaciers in Central Asia has decreased by about 30 percent over the past 50-60 years. According to Uzgidromet, there will be no significant changes in water resources in the Amudarya and Syrdarya basins by 2030, and by 2050, water resources in the Syrdarya basin will decrease by 5% and in the Amudarya basin by 15%. The total water deficit in Uzbekistan until 2015 is 3 billion. if it was over 15 billion cubic meters by 2050. can be a cubic meter [1].